Microwaves in the cold war: the Moscow embassy study and its interpretation. Review of a retrospective cohort study - Elwood J (BMC, 2012)
Abstract Background From 1953 to 1976, beams of microwaves of 2.5 to 4.0 GHz were aimed at the US embassy building in Moscow. An extensive study investigated the health of embassy staff and their families, comparing Moscow embassy staff with staff in other Eastern European US embassies. The resulting large report has never been published in peer reviewed literature. Methods The original report and other published comments or extracts from the report were reviewed. Results The extensive study reports on mortality and morbidity, recorded on medical records and by regular examinations, and on self-reported symptoms. Exposure levels were low, but similar or greater than present-day exposures to radiofrequencies sources such as cell phone base stations. The conclusions were that no adverse health effects of the radiation were shown. The study validity depends on the assumption that staff at the other embassies were not exposed to similar radiofrequencies. This has been questioned, and other interpretations of the data have been presented. Conclusions The conclusions of the original report are supported. Contrary conclusions given in some other reports are due to misinterpretation of the results.